Cholesterol Atheroembolism Syndrome: Current State of the Problem - z. D. Mikhailova; P. F. Klimkin (Архивъ внутренней медицины)
Cholesterol atheroembolism syndrome is a systemic pathological process caused by the embolization of small arteries with cholesterol crystals, which can develop spontaneously, and it is the result of intravascular surgery and / or the use of anticoagulants. Embolization cholesterol crystals leads to ischemic and inflammatory organ damage. The clinical picture is variable, various organs can be targets, but skin and kidneys are mainly affected. Specific clinical and laboratory signs aren’t. Tissue biopsy is the gold standard for diagnosis cholesterol atheroembolism syndrome. The treatment is based on the correction of classical cardiovascular risk factors, the use of statins. In terms of benefit and risk failure from anticoagulants and thrombolytics should be considered. Studies on the use of corticosteroids, cytostatic, and colchicine have conflicting results. The use of monoclonal antibodies of IL-1 antagonists is a perspective direction.